The Angiosperm Stem Hemiparasitic Genus Cassytha (Lauraceae) and Its Host Interactions: A Review - Zhang, Hongxiang; Florentine, Singarayer; Tennakoon, Kushan U. (Frontiers in Plant Science, 2022)
Cassytha, also known as “laurel dodder” or “love vine”, is a stem hemiparasite of the Lauraceae family. Whilst Cassytha has long been used for medicinal purposes in many countries, it has increasingly influenced agricultural and natural ecosystems due to its effect on a wide range of host species. It is suggested that this species might be regarded as a keystone species since it is an important element of biodiversity in natural ecosystems and can also be used as a biocontrol agent for alien plant invasion. Whilst previous studies have focused on the taxonomy and evolutionary position of different Cassytha, only the pan-tropical species Cassytha filiformis has been widely studied. The impacts of Cassytha pubescens on native and invasive host species in Australia has been recently investigated, but the other Cassytha species (ca. 17) have been rarely examined. Cassytha–host interactions are a core topic related to the understanding of the mechanisms underlying plant hemiparasitism, and ways to assess the benefits and damage caused by aerial parasitic plants at ecosystem level. This review will explore the parasitic habits, worldwide distribution and host range of Cassytha. It will further examine the impacts of parasitism on the biology of host plants, and the overall influence of environmental change on Cassytha–host associations. We also comment on areas of future research directions that requires to better understand Cassytha–host interactions.